Model wirtualny nauczania zdalnego w edukacji wczesnoszkolnej w nurcie pedagogiki Celestyna Freineta – perspektywa uczniów i nauczycieli - Abramowicz, Dawid; Kędra , Marzena; Groborz , Izabela (Studia Edukacyjne, 2021)
Remote education is not a new issue discussed in the literature, but in the face of the restrictions introduced by the COVID-19 pandemic, this type of education has developed dynamically. In the conditions of technological progress, it seems that the virtual model is particularly interesting in remote education. It was applied in March-June 2020 at the level of early childhood education at the Cogito Public Primary School in Poznań. In order to identify and evaluate remote education in the virtual model from the perspective of students and teachers, surveys with the use of an on-line questionnaire and focused group interviews were carried out.